Respostas

2013-06-06T13:21:56-03:00
A= 1 b=2 c=-3

delta = (2)ao quadrado - 4.(1).(15)
delta = 4-60
delta =56
x= -(2) +- raiz d 56
2013-06-06T14:45:17-03:00

a)    X²+2x-15 = 0

A= 1  | B= 2 | C=-15

 

Δ = b²-4*a*c

Δ = 2²-4*1*(-15)

Δ = 64

 

X= -b ± raiz quadrada de Δ/ 2*a

X= -2±8 /2

X1= -10/2 = -5

X2 = 6/2 = 3

 

 

b)      X²+4x-12 = 0

A= 1  | B= 4 | C=-12

 

Δ = b²-4*a*c

Δ = 4²-4*1*(-12)

Δ = 64

 

X= -b ± raiz quadrada de Δ/ 2*a

X= -4±8 /2

X1= -12/2 = -6

X2 = 4/2 = 2

 

 

c)    x² + 12x + 32 = 0

A= 1  | B= 12 | C=32

 

Δ = b²-4*a*c

Δ = 12²-4*1*32

Δ = 16

 

X= -b ± raiz quadrada de Δ / 2*a

X= -12±4 /2

X1= -8/2 = -4

X2 = -16/2 = -8

 

 

d)  x² + 6x - 7 = 0

 

A= 1  | B= 6 | C=-7

 

Δ = b²-4*a*c

Δ = 6²-4*1*(-7)

Δ = 64

 

X= -b ± raiz quadrada de Δ/ 2*a

X= -6±8 /2

X1= 2/2 = 1

X2 = -14/2 = -7

3 5 3